Psalm book (1937) - Språkbanken Text (University of Gothenburg, 2024)
The Swedish psalm book from 1937

Psalmboken från 1937
Psalmboken (1937)
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik